Pleurectomy/decortication and hyperthermic intrathoracic chemoperfusion using cisplatin and doxorubicin for malignant pleural mesothelioma - Klotz, Laura Valentina; Eichhorn, Martin E.; Winter, Hauke (Journal of thoracic disease, 2019)
Background: Malignant pleural mesothelioma (MPM) is an aggressive malignancy with few long-term survivors. Despite the dismal prognosis, hyperthermic intrathoracic chemoperfusion (HITHOC) was shown to improve survival in a selective group of patients. We analyzed the influence of HITHOC following pleurectomy and decortication on postoperative morbidity and overall survival for patients suffering from localized mesothelioma. - Methods: From 2009 until 2013, 71 patients with localized pleural mesothelioma underwent pleurectomy and decortication followed by HITHOC with cisplatin and doxorubicin. We analyzed postoperative morbidity, age, overall survival and influence of macroscopic resection on survival. - Results: Median patient age was 70 years (range, 65-73 years). Patients having the sarcomatoid subtype of mesothelioma showed a poor median survival of 9.2 months. In contrast, patients having the epithelioid subtype had a median survival of 17.9 months. Patients following macroscopic complete resection had a significantly better survival with 28.2 months compared to 13.1 months in patients with incomplete resection of the mesothelioma (P Conclusions: Taken together, HITHOC following pleurectomy and decortication is supposed to be a safe therapeutic option for selected patients with localized epithelial pleural mesothelioma.
Gesehen am 16.10.2019